2020
DOI: 10.3390/polym12061279
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Calcium Binding on Conformations and Motions of Anionic Polyamino Acids. Effect of Side Chain Length

Abstract: Investigation of the effect of CaCl2 salt on conformations of two anionic poly(amino acids) with different side chain lengths, poly-(α-l glutamic acid) (PGA) and poly-(α-l aspartic acid) (PASA), was performed by atomistic molecular dynamics (MD) simulations. The simulations were performed using both unbiased MD and the Hamiltonian replica exchange (HRE) method. The results show that at low CaCl2 concentration adsorption of Ca2+ ions lead to a significant chain size reduction for both PGA and PASA. With the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 102 publications
(181 reference statements)
4
13
0
Order By: Relevance
“…The brush height decreases rapidly with the addition of salt at low concentrations of CaCl2 and partially recovers at higher concentrations. This behavior is similar to what has been reported for chain sizes of free polyelectrolytes in multivalent solutions [32,69,70]. Moreover, similar to the behavior of anionic poly (amino acid) chains [32], glutamic acid brushes remain folded over a wider concentration range than aspartic acid brushes.…”
Section: The Structure Of the Brush In Cacl2 Solutionsupporting
confidence: 87%
See 3 more Smart Citations
“…The brush height decreases rapidly with the addition of salt at low concentrations of CaCl2 and partially recovers at higher concentrations. This behavior is similar to what has been reported for chain sizes of free polyelectrolytes in multivalent solutions [32,69,70]. Moreover, similar to the behavior of anionic poly (amino acid) chains [32], glutamic acid brushes remain folded over a wider concentration range than aspartic acid brushes.…”
Section: The Structure Of the Brush In Cacl2 Solutionsupporting
confidence: 87%
“…The differences in the side chains also lead to difference in brush structures in CaCl2 solutions. In the case of low grafting density at which the grafted chains do not interact by steric interactions, the behavior of the chains is similar to the behavior of polyelectrolyte chains in a multivalent salt [32,69,70]. The longer side chain of glutamic acid helps to spatially distribute the adsorbed ions inside the brush.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Recent results show, however, that this issue requires further attention. For example, despite the very similar chemical structures of the α,L-oligomers of glutamic and aspartic acids ( Figure S1a,b ), it has been shown that they interact differently with multivalent salts [ 32 , 33 , 34 ], and Thula et al have demonstrated a significant difference in organic matrix mineralization by various anionic poly(amino acids) [ 34 ]. Similarly, Picker et al have shown that aspartic and glutamic acids have qualitatively different effects on calcium carbonate crystallization [ 33 ].…”
Section: Introductionmentioning
confidence: 99%